Examining the Longitudinal Relationship between Intimate Partner Violence and Couples’ Marital Quality in Rural India - Chatterji, Sangeeta (Journal of family violence, 2023)
Much of the research on intimate partner violence (IPV) documents the negative impacts of violence on women, which are substantial. Less attention has been given to perceptions of the marital relationship given these experiences of violence. However, evidence suggests that many women affected by IPV within marriage remain in their relationships, particularly in contexts such as India, where divorce remains highly stigmatized. Understanding and supporting marital quality may need greater prioritization to support women who remain in relationships affected by violence. This study examines the association between IPV and marital quality among young married couples in rural India. We interviewed 1084 women and 1084 men at two time points (baseline, 18 months) in a western state in India and used multilevel mixed effects models to test the association between IPV and marital quality. We found that women’s experience of physical and sexual IPV was associated with poor marital quality at 18 months. Women’s experience of sexual IPV was also negatively associated with men’s self-reported marital quality at 18 months. Among men, spouse’s marital quality was positively associated with their own rating of marital quality. We also examined the reciprocal relationship between IPV and marital quality and found that women’s report of poor marital quality was associated with their future experience of physical IPV, sexual IPV, and emotional IPV. Taken together, these findings suggest that IPV interventions need to target marital quality to be effective. To do this, we would need to shift our lens from empowering individuals to empowering couples to work together to improve their relationships.